AB0393 Comparison of multi-line dot assay and enzyme-linked immunosorbent assay for detection of autoantibody profile in antiphospholipid syndrome. (23rd January 2014) - Alexandrova, E.; Reshetnyak, T. M.; Seredavkina, N. V.; Verizhnikova, Z. G.; Novikov, A. A.; Roggenbuck, D.; Nasonov, E. L.
Abstract : Background: Diagnosis of antiphospholipid syndrome (APS) still remains a laboratory challenge due to the great diversity of antiphospholipid antibodies (aPL) and their significance regarding APS classification criteria. Standardized enzyme-linked immunosorbent assay (ELISA) for antibodies to cardiolipin (aCL) and b2-glycoprotein I (ab2GPI) has been indispensable in the diagnosis and management of APS. Multiplex detection of aPL profile seems to be a new approach for risk assessment in APS. Objectives: The comparison of the novel multi-line dot assay (MLDA) with results of the routine ELISA technique for detection of aPL in APS. Methods: We studied 36 patients (pts) with APS (5 men, 31 women, median age 34, 29-44 years). Diagnosis of APS had been established according to the 2006 international classification criteria. 15 (41, 7%) APS pts met the diagnostic criteria for systemic lupus erythematosus (SLE), 28 (77, 8%) had a history of arterial and/or venous thrombosis, 21 (58, 3%) suffered from fetal loss. As a disease control group, 14 pts with SLE without APS (3 men, 11 women, median age 35, 27-45 years) were included. IgG/IgM antibodies to CL, b2GPI, phosphatidylserine (aPS) and phosphatidylinositol (aPI) in the pts sera were detected using a commercial available MLDA ("Medipan", Germany). For comparison, the serum levels of IgG/IgM aCL and ab2GPI were measured by ELISA kit ("Orgentec", Germany). Results: APS pts demonstrated a significantly higher frequency of IgG aCL, IgG and IgM ab2GPI in ELISA and IgG aCL in MLDA compared to SLE pts (p<0, 05) (table 1 ). The agreement between both methods was good for IgG aCL, IgM aCL and fair for IgG ab2GPI, IgM ab2GPI (kappa=0, 620, 0, 628, 0, 380 and 0, 388, respectively). The frequency of discrepant results for IgG aCL, IgM aCL, IgG/ IgM ab2GPI was 16%, 18% and 30%. Multiple positivity for different aPL detected by ELISA occurred significantly more frequently in APS pts (27, 8%) in contrast to SLE pts (7, 1%, p<0, 05). The number of multiple positive samples evaluated by MLDA in the APS group (13, 9%) did not demonstrated a significant higher prevalence in comparison with the control group (7, 1%, p>0, 05). There was a relationship between ischemic stroke and the combination of high positive levels of IgG/IgM aCL, ab2GPI, aPS and aPI detected by MLDA in APS pts (OR 95%CI 2, 45, 1, 09-5, 55, ρ=0, 049). We didn't find any associations between subtypes of aPL and thrombosis localization. Image/graph: Conclusions: MDLA present an alternative to ELISA for aPL evaluation and profiling in APS. The rate of false-positive aPL detected by MLDA in SLE pts was higher compared to ELISA. The combination of four high positive aPL measured by MLDA is a risk factor of ischemic stroke in APS. Disclosure of Interest: None Declared